The Semidirect Sum of Lie Algebras and Its Applications to C-KdV Hierarchy - Xia Dong; Tiecheng Xia; Desheng Li (Abstract and Applied Analysis)
By use of the loop algebra G-~, integrable coupling of C-KdV hierarchy and its bi-Hamiltonian structures are obtained by Tu scheme and the quadratic-form identity. The method can be used to produce the integrable coupling and its Hamiltonian structures to the other integrable systems.